Public web-based data monitoring and warning system using Fred node-red interface - N.N. Johari; F.P. Chee; Jedol Dayou (Faculty of Science and Natural Resources, 2020)
Constrains in data monitoring system decrease the accessibility of information by the public. Due to that, hazard warning for natural disasters related information reach late to the citizens. Improvement in this system should be made by implementing modern solution in sharing information. The Internet of Things (IoT) is the newest technology in exchanging and retrieving data between smart devices. The process of interchanging data is aided by the IoT platform such as Thing Speak, Cayenne and Blynk. Though not many of it offers to make the service reachable by unlimited users and create alert warning. FRED Node-RED (FRED) is a programmable IoT platform made to provide the availability of statistics to multi-class consumers and spread hazard warning over social network. This paper proposes to develop a public web-based data monitoring and warning system using FRED interface. To show the capability of FRED, a system that consists of sensors and Arduino Mega 2560 is built. Command is written on Arduino IDE and uploaded to the board, to obtain real-time measurements from the sensors. Node-RED then transferred the readings from hardware to FRED for displaying it on web page and send warning messages. By interfacing FRED in this system, data is visualized effectively on web page and hazard warning is posted over social network,